Accentuating dirty work: Coping with psychological taint in elite management consulting. (November 2022) - Bouwmeester, Onno; Versteeg, Barbara; van Bommel, Koen; Sturdy, Andrew
In this study, we develop the concept of dirty work by identifying new ways in which it is coped with. Traditionally, studies of dirty work have focused on how physical, social, or moral dirtiness is downplayed or normalized by workers in often physically tough "manual" occupations. We consider psychological dirtiness in work that is "knowledge intensive" and where high occupational status shields the need to protect oneself from stigma associated with dirty work. Based on interviews with management consultants working in stressful jobs in elite professional service firms, we complement the emerging literature on coping with the experience of dirty work by identifying three self- tainting tactics that consultants draw on to accentuate, rather than normalize dirty work: explication, stressing ambiguity, and humor . The motives behind these taint accentuation tactics varied from criticizing the working conditions in the sector, to the opposite, stressing one's abilities and commitment to potential clients and managers. Where dirty aspects of work have been more psychological, accentuation was used for impression management and as a form of critique. We conclude with a discussion of the wider implications for research and practice, especially in terms of how coping with dirty work is shaped by occupational context, the kind of dirtiness (physical or psychological, social or moral), and the interests of occupational audiences.